Considerations of potential vectors and animal reservoirs in an emerging cutaneous leishmaniasis area in São Domingos ranch, Paraná State in Southearn Brazil - Membrive, Norberto Assis; Hisatugo, Flora; Silveira, Thaís Gomes Verzignassi; Teixeira, Jorge Juarez Vieira; Reinhold-Castro, Kárin Rosi; Teodoro, Ueslei (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
The aim of this study was to better understand the dynamics of Leishmania sand flies and reservoirs in São Domingos ranch, Arapongas municipality, Paraná State, an anthropic environment in an endemic area of cutaneous leishmaniasis (CL). Sand flies were collected in wild animal burrows, residences and in the forest, with Falcão light trap (FA), Shannon trap (SH) and quadrangular pyramidal trap (QP). The search for Leishmania was made on sand flies, biological samples of wild rodents and dogs using PCR and culture; while parasite direct search (DS) was carried out on animal skin lesions; infection of gold hamsters; and indirect immunofluorescence (IIF) test in dog blood samples. Eighty eight (88) sand flies were collected with FA traps and 526 sand flies using the SH trap, with a predominance of Pintomyia fischeri. Six hundred and one (601) specimens of Brumptomyia brumpti were collected in armadillo burrows, with the QP trap. Seventeen (17) wild rodents were captured, six of them had skin lesions with characteristics of Leishmania infection. Even though no positive test was found for Leishmania, epidemiological surveillance should be maintained, remembering that the human buildings are situated only 50 m from the forest. Considering the species of wild animals and sandflies found in São Domingos, the negative test found do not exclude the existence of the Leishmania transmission cycle in this preservation area.